Green Human Resource Management in Bangladesh: Practices, Environmental Impacts, Accounting Integration, and Challenges - Sultana, Fatema; A.K.M. Moniruzzaman (The International Journal of Accounting and Business Society, 2025)
Purpose -This paper examines the current state of Green Human Resource Management (GHRM) in Bangladesh and explores its linkages with environmental and financial performance, particularly in the textile/garment (RMG), banking, and manufacturing industries. Design - A narrative review method was adopted, drawing on multiple databases (Scopus, Web of Science, JSTOR, Google Scholar, and ProQuest) to analyze both peer-reviewed and grey literature. The review integrates findings to highlight practices, policies, and sectoral variations, as well as the interplay between GHRM, accounting, and financial reporting. Findings- Results reveal that GHRM practices positively influence environmental performance, employee environmental behavior, and organizational sustainability. Some evidence indicates that accounting benefits include cost control, risk minimization, and reputation enhancement. However, explicit financial measures (e.g., cost accounting of environmental outcomes, integration with management control systems) remain underexplored. Adoption is uneven across sectors and constrained by limited managerial commitment, technical capacity, regulatory inefficiency, and resource shortages. Practical implications: Effective GHRM implementation requires simultaneous attention to organizational and technological innovation, as well as integration with accounting and reporting systems. Policymakers and managers must address regulatory gaps, provide sector-specific guidelines, and strengthen capacity to maximize both environmental and financial gains. Originality- This study provides one of the first comprehensive accounts of GHRM practices in Bangladesh, emphasizing its intersection with accounting and financial performance. It contributes to scholarship and practice by identifying gaps, challenges, and policy directions relevant to emerging economies and multinational subsidiary operations. Paper type- Narrative Review